(untitled) (CIPEEX, 2025)
Concrete remains one of the most widely used construction materials, yet its environmental impact and the demand for improved mechanical performance have led to the search for sustainable alternatives. This study aims to evaluate the potential of natural fibers as reinforcement in concrete, with focus on coconut, sisal, and bamboo fibers. Compressive strength tests were conducted using a hydraulic press, and the performance of each fiber type was analyzed. Results showed that coconut fiber, although not superior in compressive strength, contributed to improved durability and tensile resistance. Sisal fiber demonstrated comparable compressive strength to conventional concrete, reaching values up to 35 MPa, proving to be a viable reinforcement option. Bamboo fiber stood out by achieving superior compressive strength when properly treated, rivaling even high-performance concretes. These findings indicate that the incorporation of natural fibers into concrete not only enhances its mechanical properties but also promotes eco-friendly construction practices. The conclusions highlight bamboo as the most promising alternative due to its strength, sustainability, and potential to reduce the environmental footprint of civil engineering projects.